Burnout in hospital healthcare workers after the second COVID-19 wave: Job tenure as a potential protective factor - Antao, Helena Sofia; Sacadura-Leite, Ema; Correia, Ana Isabel; Figueira, Maria Luisa (Frontiers in Psychology, 2022)
Burnout is an impactful occupational health phenomenon to which doctors and nurses have been more exposed during the COVID-19 pandemic. The objectives of this study were to measure the dimensions of burnout - emotional exhaustion, depersonalization and personal accomplishment - in a hospital healthcare population after the 2nd COVID-19 wave and to study their association with socio-demographic variables and previous COVID-19 infection. We invited 112 healthcare professionals (doctors and nurses) who attended the occupational health department of a tertiary hospital in March-July 2021. Emotional exhaustion, depersonalization and personal accomplishment were measured by the Maslach Burnout Inventory. Linear-regression analyses were conducted to explore relationships between burnout dimensions and sociodemographic variables. Differences between groups according to previous COVID-19 infection were verified using the t-test and when appropriate the Mann-Whitney test (for continuous variables), the chi-square test and when appropriate the Fisher exact test (for categorical variables). We surveyed 106 subjects (95% response rate). High emotional exhaustion and depersonalization were reported by 33.0% and 18.4% of participants, respectively; 21.4% reported low personal accomplishment. Job tenure was associated with depersonalization and personal accomplishment. For each 1-year increase in job tenure, depersonalization decreases 0.14 (95% CI [-0.23, -0.04]) and personal accomplishment increases 0.16 (95% CI [0.06, 0.25]). Gender was associated with emotional exhaustion (being male increases emotional exhaustion 5.62-fold [95% CI: 1.33; 9.92]). The prevalence of high emotional exhaustion, high depersonalization and low personal accomplishment after the 2nd COVID-19 wave was relevant and should not be overlooked. Our findings suggest that job tenure may play a protective role in healthcare workers’ burnout.